Low GABA concentrations in occipital cortex and anterior cingulate cortex in medication-free, recovered depressed patients. - Bhagwagar, Z; Wylezinska, M; Jezzard, P; Evans, J; Boorman, E; M Matthews, P; J Cowen, P (2008)
Studies using proton magnetic resonance spectroscopy (1H-MRS) indicate that unmedicated, acutely depressed patients have decreased levels of gamma-aminobutyric acid (GABA) in the occipital cortex. The aim of this study was to use 1H-MRS to determine if changes in occipital and frontal cortical GABA levels were present in patients with a history of depression who had recovered and were no longer taking medication. We used 1H-MRS to measure levels of GABA in both occipital cortex and anterior cingulate cortex/prefrontal cortex in medication-free, fully recovered subjects with a history of recurrent unipolar depression. Levels of GABA in both occipital and anterior cingulate cortex were significantly lower in recovered depressed subjects than healthy controls. Our data provide preliminary evidence that a history of recurrent depression is associated with decreased GABA levels in anterior cingulate cortex and occipital cortex. These changes could represent part of the neurobiological vulnerability to recurrent depressive episodes.